The metabolic and endocrine response to trauma. Issue 8 (August 2020) - Krepska, Amy; Hastings, Jennifer; Roodenburg, Owen
Abstract: Metabolic and endocrine pathways are central to the body's compensatory response to trauma. They drive mobilization of energy substrates, volume conservation and haemostasis via activation of the hypothalamic pituitary adrenal axis, the sympathetic nervous system and an inflammatory response. As clinicians, we can intervene in these pathways, however optimal management of anaesthesia, fluids, transfusion, nutrition and the use of steroids remains controversial and to be determined.